2011
DOI: 10.1093/nar/gkr753
|View full text |Cite
|
Sign up to set email alerts
|

Function and disruption of DNA Methyltransferase 3a cooperative DNA binding and nucleoprotein filament formation

Abstract: The catalytic domain of Dnmt3a cooperatively multimerizes on DNA forming nucleoprotein filaments. Based on modeling, we identified the interface of Dnmt3a complexes binding next to each other on the DNA and disrupted it by charge reversal of critical residues. This prevented cooperative DNA binding and multimerization of Dnmt3a on the DNA, as shown by the loss of cooperative complex formation in electrophoretic mobility shift assay, the loss of cooperativity in DNA binding in solution, the loss of a characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 41 publications
5
52
1
Order By: Relevance
“…In contrast, as shown previously, binding to a 60-mer substrate was cooperative, as indicated by the fact that the binding curve was sigmoidal and could only be fitted with a Hill coefficient of 2.2 ( Fig. 2C) (14). Based on these results, we conclude that binding of Dnmt3a-C to the 29-mer DNA shows only a very weak cooperativity, indicating that an oligonucleotide of this size can be used as a reference substrate to study Dnmt3a-C methylation The in Vitro Catalytic Turnover Rate of Dnmt3a-C Is Increased on a Long DNA Substrate-Having shown that DNA binding to the short oligonucleotides shows very low cooperativity, we next determined the enzymatic rate of DNA methylation using two biotinylated substrates of different length, a 30-bp oligonucleotide containing one CpG site (at 250 nM) (that has been used as "standard" substrate in many of our studies before) and a 509-bp long substrate that corresponds to a part of the CpG island upstream of the human SUHW1 gene and contains 58 CpG sites (at 100 nM).…”
Section: Resultscontrasting
confidence: 47%
See 4 more Smart Citations
“…In contrast, as shown previously, binding to a 60-mer substrate was cooperative, as indicated by the fact that the binding curve was sigmoidal and could only be fitted with a Hill coefficient of 2.2 ( Fig. 2C) (14). Based on these results, we conclude that binding of Dnmt3a-C to the 29-mer DNA shows only a very weak cooperativity, indicating that an oligonucleotide of this size can be used as a reference substrate to study Dnmt3a-C methylation The in Vitro Catalytic Turnover Rate of Dnmt3a-C Is Increased on a Long DNA Substrate-Having shown that DNA binding to the short oligonucleotides shows very low cooperativity, we next determined the enzymatic rate of DNA methylation using two biotinylated substrates of different length, a 30-bp oligonucleotide containing one CpG site (at 250 nM) (that has been used as "standard" substrate in many of our studies before) and a 509-bp long substrate that corresponds to a part of the CpG island upstream of the human SUHW1 gene and contains 58 CpG sites (at 100 nM).…”
Section: Resultscontrasting
confidence: 47%
“…Therefore, we aimed to determine the DNA methylation rates on a long substrate that allows cooperative DNA binding and protein/ DNA fiber formation and compare it with the methylation rate on a short substrate that does not support fiber formation. Previous biochemical and structural data indicated that one Dnmt3a-C complex (consisting of four or more Dnmt3a-C molecules) contacts the DNA with its inner two subunits and methylates cytosine residues in the upper and lower DNA strand located at a distance of 8 -10 bp (10,11,14). DNA binding of these Dnmt3a complexes occurs in a tilted fashion such that adjacent complexes can bind the upper and lower cytosine of one CpG site.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations